2014
DOI: 10.3375/043.034.0213
|View full text |Cite
|
Sign up to set email alerts
|

Timing is Everything: An Overview of Phenological Changes to Plants and Their Pollinators

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 50 publications
(65 reference statements)
1
28
0
Order By: Relevance
“…Previous studies have shown that plants alter their growth and phenology under different agricultural contexts (Campbell et al, 2013;Craufurd and Wheeler, 2009;Cresswell, 2000;Solga et al, 2014;Williams and Thomson, 2001), which can present a serious problem during the introduction of an agricultural crop to a novel region. In the present study, although the melon cultivars were not initially developed for cultivation in the Cerrado regions, all the melon cultivars (except the 'Hibrix' cultivar) showed feasibility for production under Cerrado conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that plants alter their growth and phenology under different agricultural contexts (Campbell et al, 2013;Craufurd and Wheeler, 2009;Cresswell, 2000;Solga et al, 2014;Williams and Thomson, 2001), which can present a serious problem during the introduction of an agricultural crop to a novel region. In the present study, although the melon cultivars were not initially developed for cultivation in the Cerrado regions, all the melon cultivars (except the 'Hibrix' cultivar) showed feasibility for production under Cerrado conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Such traits might affect the performance of this horticultural crop by affecting the production and the quality of the fruit. Furthermore, because flower morphology (e.g., flower length, and calyx and corolla width) and phenology are traits that respond to environmental cues (Campbell et al, 2013;Craufurd and Wheeler, 2009;Cresswell, 2000;Solga et al, 2014;Williams and Thomson, 2001), the findings of this study might also assist in assessing the feasibility of commercial production of melon in the Cerrado regions, as the diverse melon cultivars introduced yearly in the market were initially not developed to be cropped under these climatic (e.g., temperature, photoperiod, and precipitation) and biotic (e.g., pollinator richness and pollination efficiency) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the greater advances were observed in the availability of resources to flies (nectar and pollen), butterflies (nectar), and wasps (nectar and pollen); and the greater delay in the availability of resource to beetles (pollen) indicate a stronger influence of fire on plant-animal pollination interactions. In fact, it is possible that a temporal mismatch may occur between plant and pollinator phenologies (Peñuelas and Filella 2001;Memmott et al 2007;Solga et al 2014), since both nectar and pollen availability may not coincide with the period of natural pollinator activity (Bawa 1990;Hegland et al 2009). It is notable that there were virtually no flowering individuals in the month after fire, which may represent a transient negative effect of fire on resource availability to those pollinator groups caused by the destruction of flower buds (Hoffmann 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Negative consequences are also associated with plant species supporting moths, of which there were very few individuals that provided suitable nectar, and showed a delay in nectar availability by three months. Moths are seasonally active, which may break the natural synchrony between plant and pollinator phenologies (Peñuelas and Filella 2001;Memmott et al 2007;Solga et al 2014). Also, the small nectar availability to moths is observed all year round in both scenarios (with and without the effects of fire), and moth-pollinated species are not particularly abundant in cerrado, possibly as a consequence of fire affecting this plant-animal mutualism (Bond 1994;Kearns and Inouye 1997;Potts et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation